2013
DOI: 10.1073/pnas.1301690110
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Drosophila Polo kinase to its regulator Matrimony is noncanonical and involves two separate functional domains

Abstract: Significance Polo kinase regulates many processes during cell division and is upregulated in many cancers. During Drosophila female meiosis, the protein Matrimony inhibits Polo kinase using a noncanonical mechanism of Polo binding. Complete loss of Matrimony leads to meiotic catastrophe, and partial loss leads to chromosome missegregation. Proper Matrimony–Polo binding is required to prevent these defects, indicating that preventing Polo from phosphorylating targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 36 publications
5
50
0
Order By: Relevance
“…Paradoxically the pI shift between the foci appears to be much larger than expected for the addition of a single phosphate group. In contrast, our own analysis of S2R+ cells identified multiple Cnn-LF foci with an average pI shift between foci of 0.2, consistent with the addition of multiple single phosphate groups to the Cnn-PA splice variant, precisely as predicted by ProMoST (Bonner et al 2013) (http://proteomics.mcw. edu/promost.html) (also see Figure S2).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Paradoxically the pI shift between the foci appears to be much larger than expected for the addition of a single phosphate group. In contrast, our own analysis of S2R+ cells identified multiple Cnn-LF foci with an average pI shift between foci of 0.2, consistent with the addition of multiple single phosphate groups to the Cnn-PA splice variant, precisely as predicted by ProMoST (Bonner et al 2013) (http://proteomics.mcw. edu/promost.html) (also see Figure S2).…”
Section: Discussionmentioning
confidence: 71%
“…High-affinity binding sites have a proline at the +1 position but an in-depth analysis of Plk1 target substrates found 30% of targets had low-affinity sites, suggesting the binding sites were primed by a kinase other than CDK1 or did not require phosphopriming (Santamaria et al 2011). Additionally, the Polo inhibitor Map205 binds to Polo at the PBD but does not require phosphopriming (Archambault et al 2008) and the encoded inhibitor Matrimony binds to Polo via a noncanonical mechanism (Bonner et al 2013). Clearly Polo can interact with target substrates by more than one mechanism.…”
mentioning
confidence: 99%
“…Mtrm-T40A is unable to bind Polo, and cannot rescue chromosome nondisjunction in mtrm/+ heterozygotes [28],[38]. In contrast to wild-type Matrimony, expression of Mtrm-T40A did not cause any developmental defects (Figure 5H).…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies have shown that Plk kinase activity can be limited to brief periods within the cell cycle through mechanisms involving the transcription, localization, degradation, and autoinhibition of the kinase (3,(10)(11)(12)(13). New regulatory mechanisms of Plks continue to be identified (14)(15)(16), making it clear that our understanding of Plk regulation is incomplete.…”
mentioning
confidence: 99%